The Concept of Wasathiyah in Islam: A Study of Religious Moderation in Indonesia - Nahrowi Nahrowi; Siti Ropiah; Dede Fakhruddin; Mustopa Mustopa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine in depth the concept of wasathiyah in Islam as the foundation of religious moderation in Indonesia. The main focus of this research is to analyze the core values of wasathiyah such as justice, balance, tolerance, and deliberation, and to explore how these values are implemented within the socio-religious context of Indonesia’s plural society. The objective of this study is to understand the relevance of wasathiyah teachings in strengthening interreligious harmony and contributing to the establishment of a peaceful and inclusive religious life amidst challenges of radicalism and intolerance. The research employs a qualitative descriptive approach using a library research method. Data were collected from scientific journals, books, previous research findings, and official documents from the Ministry of Religious Affairs of the Republic of Indonesia discussing religious moderation and wasathiyah. Data analysis was conducted through content analysis to identify main themes and correlations between the normative concept of wasathiyah and socio-religious practices in Indonesia. The findings reveal that wasathiyah is not merely a theological concept but also a social paradigm emphasizing balance between creed, worship, and social relations (muamalah). The values of wasathiyah are reflected in various national policies and programs such as strengthening religious moderation, multicultural education, and interfaith dialogue. The application of wasathiyah values has proven effective in preventing social polarization and reinforcing interreligious cohesion in Indonesia. The study concludes that the concept of wasathiyah serves as a fundamental basis for religious moderation in Indonesia. The internalization of wasathiyah values should be systematically implemented through religious education, public policy, and the exemplary leadership of community figures. Consistent implementation will strengthen the nation’s character as tolerant, just, and civilized. The implications of this study highlight the importance of synergy among educational institutions, government bodies, and religious leaders in mainstreaming wasathiyah as a religious culture. This research also serves as an academic reference for developing religious moderation curricula and deradicalization strategies based on the Islamic values of rahmatan lil ‘alamin (mercy to all creation).